Participação de terceiros no processo civil eleitoral - Rangel, Marco Aurélio Scampini Siqueira (2015)
This thesis aims to analyze the participation of third parties in the electoral process. Throughout the work will be made the analysis of the current state of the electoral process and the need to approach from the perspective of collective process. Established such premises will be possible to systematize the electoral action and its elements. In addition, this study will also address the characteristics of third party intervention procedures laid down in the Code of Civil Procedure and the difficulty of their application into the electoral process. Finally, will be demonstrated the situation in which is accepted third-party participation in the electoral process.